Pentingnya Pendidikan Karakter dalam Meningkatkan Kualitas Pembelajaran Peserta Didik - Putri Utami (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Character education serves as a vital component in shaping students who excel not only in academics but also possess commendable character and strong ethical values. The aim of this research is to examine the significance of character education in enhancing student learning quality, along with the involvement of teachers and parents in its execution. This research adopts a literature review approach, employing a qualitative descriptive analysis method grounded in expert perspectives. The findings reveal that character education plays a pivotal role in developing positive traits in students, including honesty, accountability, discipline, and integrity. The teacher’s function as a motivator and facilitator in the learning journey, and the parent’s function as the initial educators, heavily influence the effectiveness of character education. This research concludes that embedding character education must begin at an early stage through collaboration between the school and the family, enabling students to evolve into capable, resilient individuals who can thrive in the modern age.